A Quantitative Examination of Georgia High School CCRPI Scores and School-Level Student Demographics Using Multiple Regression Analysis - Wiley, Jonathan (My University, 2019)
This dissertation study was conducted using multiple regression analysis to determine the degree to which school-level variables of percentage of minority students, percentage of students with limited English proficiency, percentage of economically disadvantaged students, percentage of students with a disability, and percentage of gifted students significantly predict the school’s performance measure on Georgia’s College and Career Ready Performance Index (CCRPI) for the school years 2012-2018. Data from public high schools composed of grades 9-12 across the state of Georgia were collected and analyzed. Results showed that a school’s percentage of gifted students, percentage of economically disadvantaged students, and percentage of minority students were significant predictors of CCRPI scores across all seven years examined. For two of the seven years, a school’s percentage of students with a disability was also a significant predictor of CCRPI scores. Findings from this study suggest the school’s CCRPI scores are negatively affected by students of a racial/ethnic minority, students at an economic disadvantage, and at times, students with a disability. Findings from this study also show a school’s percentage of gifted students positively affects the school’s CCRPI scores.
CHAPTER I: INTRODUCTION 1 -- Problem Statement 3 -- Purpose 6 -- Research Questions 7 -- Theoretical Framework 8 -- Methodology 11 -- Significance 12 -- Limitations, Delimitations, and Assumptions 14 -- Limitations 14 -- Delimitations 15 -- Assumptions 15 -- Definition of Key Terms 16 -- CHAPTER II: REVIEW OF LITERATURE 19 -- Historical Context 20 -- Ambiguity in Data Interpretations 21 -- New School Accountability Measures in Georgia 23 -- Cultural Ecological Theory 26 -- Student Demographics as Predictor Variables 28 -- Race/Ethnicity 30 -- Limited English Proficiency 34 -- Economically Disadvantaged Students 38 -- Disability Status 43 -- Gifted Status 46 -- Summary 49 -- CHAPTER III: METHODOLOGY 51 -- Research Questions 51 -- Research Design 52 -- Population 53 -- Participants and Sampling 54 -- Instrumentation, Validity, and Reliability 55 -- Instrumentation 55 -- Validity 56 -- Reliability 56 -- Independent Variables and Dependent Variables 58 -- Independent Variables 58 -- Dependent Variables 58 -- Data Collection 58 -- Data Analysis 59 -- Summary 63 -- CHAPTER IV: DATA ANALYSIS 65 -- Descriptive Statistics 66 -- Research Question 1 70 -- Research Question 1a 70 -- Research Question 1b 72 -- Research Question 1c 73 -- Research Question 1d 75 -- Research Question 1e 76 -- Research Question 2 78 -- School Year 2012 79 -- School Year 2013 80 -- School Year 2014 82 -- School Year 2015 84 -- School Year 2016 85 -- School Year 2017 87 -- School Year 2018 89 -- Summary 91 -- CHAPTER V: CONCLUSIONS, IMPLICATIONS, AND RECOMMENDATIONS 93 -- Discussions of the Findings 93 -- Implications for Theory and Practice 101 -- Limitations and Recommendations for Future Research 103 -- Conclusions 105 -- APPENDIX A: Institutional Review Board Approval 123 -- APPENDIX B: Descriptive Statistics for School Years 2012-2018 125 -- APPENDIX C: Test Results of Regression Assumptions for School Years 2012-2018. 142.
Keywords: Dissertations, Academic--United States; Education, Secondary; Educational tests and measurements; Georgia; Quantitative research; Regression analysis